The politics of the unpolitical : German writers and the problem of power, 1770-1871 - Craig, Gordon Alexander, 1913-2005 (Oxford University Press, 1995)
Craig deals with a question that has always been a point of controversy: do political writers have responsibility and are they obliged to show political engagement in their works? Craig answers this question by studying ten German writers from 1770-1871, among them Goethe, Schiller, Kleist, and Heine and finds that these 'unpolitical' writers were actively engaged in their politics.